Spiral staircase, David Sassoon Clocktower - Ghosh, Ayan (2023)
The David Sassoon Clock Tower was constructed by Messrs. Scott, McClelland and Co., who also completed the Victoria and Albert Museum after its architect William Tracey died. In both buildings, they used the Neo-Palladian style, lending architectural uniformity in the buildings. The ensemble of buildings at Jijamata Udyan, which includes the triple-arched gateway, are the only buildings in Mumbai where the Palladian architectural style was used.